Analysis of China's real estate prices and macroeconomy based on evolutionary co-spectral method - Juan Li; Xuemin Chen (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: This paper investigates the dynamic interaction between the real estate market and the macroeconomic environment of China by use of dynamic coherence function based on co-spectral analysis. Design/methodology/approach: Through a theoretical perspective, the dynamic interrelationship among economic variables at different time intervals (both long and short terms) is analyzed. Findings: The empirical results show that China's real estate market features a high coherence with the change of the long-term interest rate, employment rate and money supply, while there is a moderate coherence between the real estate market and the inflation rate and economic growth rate, and the coherence between the short-term rate of interest and the real estate market is the lowest. Research implications: Previous researches have some shortcomings. They do not consider the dependence between nonlinear series, but the latter is crucial to avoid the deviation of results. In this paper, we proposed a new method of experience to overcome these shortcomings. Originality/value: The paper provides a reasonable explanation accordingly to different coherences between the real estate market and the macroeconomic variables.
Keywords: 650; real estate; macroeconomy; dynamic coherence function; monetary policy